Literatura y poder: García Márquez en México (1961-2014). Literature and power: García Márquez in Mexico (1961-2014) - Pineda Buitrago, Sebastián (Latinoamérica. Revista de Estudios Latinoamericanos, 2017)
El objetivo de este artículo es explorar parte del contexto intelectual alrededor de la obra periodística o de no-ficción del escritor colombiano Gabriel García Márquez (1927- 2014) a partir de su estancia en México entre 1961 y 2014. Dos preguntas se intentarán contestar en este artículo: 1) ¿Por qué, a pesar de haber residido tanto tiempo en México, el escritor colombiano poco opinó sobre la realidad mexicana? 2) ¿Hay realmente una diferencia entre el “realismo mágico” de sus novelas y la referencialidad histórica de sus crónicas o artículos periodísticos? Abstract: This article looks into the intellectual context of the journalistic or non-fiction writings of Gabriel García Márquez (1927-2014), those that resulted from his experiences in Mexico between 1961 and 2014. This essay will address two questions: 1) Why did Garcia Márquez not write a considerable amount of journalistic work about Mexico despite the fact that he lived such a long time in the country? 2) Is there really a difference between the “magical realism” of his novels and the historical referentiality of his newspaper articles?